Historical implications of ‘war on terror’ to politics and policy of Iraq, Syria, and Afghanistan - Darawan Abdulqader Ahmed (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
Over the past few decades, the Middle East has been plagued by a series of conflicts linked to terrorism, which have disrupted the stability of several countries in the region. Since the war on terrorism was declared, terrorism has influenced politics and policy in the Middle East. Furthermore, terrorism has also hindered economic prosperity, development, and social welfare in countries caught up in conflict. This article aims to examine terrorism and its impact on the political and policy spheres in the Middle East, specifically in the selected countries: Syria, Iraq, and Afghanistan. This article uses a case study method to examine this topic in detail for each country. This article utilizes several global indices, including the Global Terrorism Index 2017–2024, the Global Peace Index, the Conflict Index, the Fragile States Index, and the Failed States Index. The findings indicate that regime change, clashes over ethnic and religious differences, and regional power politics are the underlying causes of the ongoing conflicts in the Middle East. Based on the findings of this study, it can be concluded that the context and conditions of Iraq, Syria, and Afghanistan as post-conflict states remain fragile and are influenced by terrorism, the impact of the war on terror, and regional competition, which have serious long-term implications for each country. This article contributes to the development of the Regional Security Complex Theory by Buzan and Waver (2003) regarding the War on Terrorism, which relates to the Middle East security dilemma and the balance of power.